Between prescribed and real: the role of subjectivity in the realization of the rights of domestic workers in Brazil - GIRARD-NUNES, Christiane; SILVA, Pedro Henrique Isaac (Sociedade e estado, 2013)
In recent years, significant changes are being processed in the scope of work in Brazil: more formalization of employees, real increase of worker's income and the expansion of rights through new sectors, like those of domestic workers. The supporter that makes possible - not the only one - the expansion of rights is the recognition of values which were not contemplated until now, in a social context partially favorable and with many struggles and pressures. This article analyzes some aspects of the paradox between the establishment of new rights and the actual appropriation of them. This gap between what de law prescribes and the reality of the work requires attention to the several rationalities that exist in this labor market and often call into question the progress of society in the struggle for equity. The analysis shows that there is progress and obstacles in the implementation of domestic workers' rights. Furthermore, it is necessary that domestic workers are able to become Subject of right, and not only an object of policies, for the current development choice may generates the expected results. Adapted from the source document.